Promoting access to medical technologies and innovation : intersections between public health, intellectual property, and trade - Bartels, Hans G. (World Health Organization : World Intellectual Property Organization : World Trade Organization, 2020)
The revised study records the numerous significant developments that we have seen since 2013. These include efforts made towards achieving universal health coverage, challenges posed by antimicrobial resistance, the changing disease burden and new global disease threats. The study reviews public and private sector innovation models, as well as the repercussions of an increasingly diverse medical technologies industry and the rise of innovative and production capacity in developing countries. It draws practical lessons from experiences regarding how public health, IP, trade and competition rules all interact with each other in the broader context of the human rights dimension of health and the United Nations' Sustainable Development Goals (SDGs). And it provides insights on measures to promote innovation and access to medical technologies, noting the growing network of free trade agreements and the importance that trade plays for access to medical technologies.
"Research, authoring and substantive review was done by: Hans Georg Bartels [and 8 others]"--Page 5.
Keywords: Medical technology.; Medical innovations.; Public health.; Intellectual property.; Commerce.; Pandemics.; COVID-19 (Disease); Biomedical Technology -- methods.; Intellectual Property.; Public Health -- standards.; Technologie médicale.; Médecine -- Innovations.; Santé publique.; Propriété intellectuelle.; Pandémies.; COVID-19.; public health.; intellectual property.; pandemics.; Commerce; Intellectual property; Medical innovations; Medical technology; Pandemics; Public health